2021
DOI: 10.1021/acs.orglett.1c03295
|View full text |Cite
|
Sign up to set email alerts
|

Diindeno[2,1-b:2′,1′-h]biphenylenes: Syntheses, Structural Analyses, and Properties

Abstract: A series of diindeno­[2,1-b:2′,1′-h]­biphenylenes with open-shell singlet ground states and interesting properties were prepared. The studied compounds consist of p-quinodimethane moieties, which suffer from geometric perturbation with bond angles of around 90°. The substituent effects on structural parameters, local aromaticity, and properties were systematically explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In a recent paper, Chen et al reported the synthesis, structural analyses, and properties of some derivatives of diindeno­[2,1- b :2′,1′- h ]­biphenylene ( 1a ) . Among these properties, the aromatic properties of the system were analyzed using the harmonic oscillator model of aromaticity (HOMA) and nucleus-independent chemical shifts (NICS(1)) as “local aromaticity” indicators and the gauge-including magnetically induced current method (GIMIC).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent paper, Chen et al reported the synthesis, structural analyses, and properties of some derivatives of diindeno­[2,1- b :2′,1′- h ]­biphenylene ( 1a ) . Among these properties, the aromatic properties of the system were analyzed using the harmonic oscillator model of aromaticity (HOMA) and nucleus-independent chemical shifts (NICS(1)) as “local aromaticity” indicators and the gauge-including magnetically induced current method (GIMIC).…”
Section: Methodsmentioning
confidence: 99%
“…Cutting it rather arbitrarily (according to some σ bonds) may result in erroneous aromaticity assignments. (c) Principally, GIMIC describes the induced currents in the system (locally and globally); however, it cannot separate π current from σ current (and is therefore less appropriate for aromaticity studies), and the way that the GIMIC results are reported in ref (Supporting Information) does not allow one to get a picture of the types of currents (i.e., local, semiglobal, and global) in the system.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18][19][20][21] The variation in the chemical functionality yields copious D and A building blocks. [22][23][24][25][26][27][28] The change in the linking mode provides distinct molecular architectures. [29][30][31] Side-chain engineering regulates intermolecular interactions.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, antiaromatic unit-embedded PAs bearing a (4 n + 2)­π-electron perimeter with dominant contribution from its antiaromatic subunit are underexplored, with limited examples of quinoidal dicyclopenta­[ a , e ]­pentalene, bispentalenes, s -IDFs, , and phenylene-based acenes, while pentalenodifluorene, dibenzo- s -IDF, and diindenobiphenylene displayed open-shell ground state instead of antiaromaticity. Therefore, (4 n + 2)­π-systems made of antiaromatic subunits are of special interest, but their heteroaromatic analogues are unknown.…”
mentioning
confidence: 99%